Complex training methodology increases standard of amateurs boxing for senior - Bushati, S. (European Journal of Multidisciplinary Studies, 2020)
The presented research reflects an aspect of the training process with the amateur boxing champion team of sports club "Tirana" of Albania, for 2019, in which prominent boxers have been prepared, who are worthily represented in national and international activities, winning medals national. Normalization and modeling of the training process in a complex way according to special preparation cycles, in order to qualitatively develop the training indicators, in accordance with the physical, physiological and psychological requirements set by amateur boxing for senior. Experimentation; an original complex training methodology based on macrocycles was experimented, which are divided in 4 phases (adapter, developer, reinforcer and perfection) with senior amateur sports club boxers . "Tirana", within a period of one year (January 6, 2019 to December 31, 2019 ), Athletes are tested 3 times during the year at the beginning, between and the finish.Where they are tested indicators physical movements, special functional and Leonardo platforms are tested. It is worth mentioning the developments in physical , technical and functional indicators,, where there was an average increase of 8.1%. N Special test with the first two exercises, marked a rise of 14.9% (8:44% in the amount of repetitions, 2:26 in the blinking% in cargo and 4:20 in the blinking% after one minute) . In Drop-jump test was a marked increase in h 7:55%. In testig Singel 2 Leg Jump (assisted), at 6.54% (FFI, at 5.96%, Jump Height, at 7.55% and Efficiency, at 6.12%). In the Singel leg Jumnp test (without assistance): 6.17% (where F.Mes, Rel, at 7.69%, F.Mes.Rel / weight, at 9.73% and A. C ontakt time, at 1.09%). Conclusion: N of the training process should take advantage character loads pronounced aqnaerobik physiological during which prevailing energy processes anaerobic against those aerobic (process anaerobic alaktik, at 10%, anaerbik process lactic glikolitik, 60% and aerobic process, to the extent 30%).